The upper limb of the North Atlantic overturning circulation : investigation of the subtropical-subpolar gyre exchange and Subpolar Mode Water - Brambilla, Elena (eScholarship, University of California, 2006)
Two aspects of the upper limb of the North Atlantic overturning circulation are studied: 1) surface drifter exchange between the subtropical and the subpolar gyres; and 2) characterization of the properties and formation of Subpolar Mode Waters (SPMW). With respect to the first, just one out of 273 drifters (drogued at 15 m) in the Gulf Stream region from 1990 to 2002, moved from subtropical to subpolar latitudes. Most of the drifters recirculated in the subtropical gyre without crossing the inter-gyre edge. This result was surprising because of the known transport of upper ocean water from the subtropical to the subpolar gyre. We suggest that undersampling and inadequate drifter life time lead to an underestimate the northward flow. Moreover, the Ekman flow and the eddy contribution affect the surface trajectories in opposite direction, nearly canceling each other. The description of the properties of the SPMW and the analysis of its formation aim at better describing the warm and salty pathway that supplies water to the regions of dense water formation (Labrador and Nordic Seas). Lagrangian data (surface drifters and isopycnal floats) combined with historical hydrographic data show that each branch of the North Atlantic Current (NAC) in the eastern subpolar gyre is characterized by its own sequence of SPMW that increases in density following the downstream flow. Furthermore, since the branches of the NAC have a dominant northeastward direction, the newly observed distribution of SPMW, combined with the new streamfunctions calculated here, do not support the original hypothesis of (McCartney and Talley, 1982) of a smooth, cyclonic pathway for SPMW around the subpolar gyre. The transformation and the formation of SPMW are then investigated in terms of the diapycnal flux driven by buoyancy flux. We show that SPMW is transformed to increasingly dense SPMW along the major branches of the NAC. The continuous transformation of SPMW is not constant in density space, leading to ̀̀formation'' (destruction) of SPMW. However, since the SPMWs are shown to be confined within the mixed layer, we interpret the SPMW formation as loss by entrainment to the dense overflows through Denmark Strait and Iceland_Scotland Ridge